Oral History Versus Oral Tradition - Soegijanto Padmo (Humaniora, 1998)
When in 1974, a religious teacher tried to reopen a religious school in Kedung Turi Village, Plasa Sub-District which had been in operation in the northern area since the mid of the 19th century. Since there is no relation in many respects between the newly emerged kyai in Kedung Turi and the relatively settled-down older kyais of southern part, namely in Tebuirang, Tambakberas, and the surrounding villages, they declared that the kyai of Kedung Turi is not a genuine kyai. In this paper, an attempt is made to discover why the Kedung Turi religious school is considered as not a genuine pesantren and the kyai is not a genuine kyai and how it developed within period of relatively in relatively short period of time has been attracting so many followers.